QUESTIONING STRATEGIES IN EFL CLASSROOM: THE TEACHER’S PERCEPTIONS - Indri Astutik; Novi Indriani; Nurkamilah (UMBanjarmasin, 2021)
A crucial ability expected of EFL students is a critical and creative thinking ability. Questioning method is regarded as the most important technique for encouraging students to build this ability. Because the students are anxious about making mistakes, they remain silent when teachers ask them. Thus, using questioning strategies in giving questions can be a way to engage them in interactive activities. This research, therefore, was aimed to investigate teacher’s questioning strategies in teaching English and the reasons for using them. This study employed qualitative descriptive design by conducting an online interview and giving questionnaire to an English teacher of a private junior high school in Jember. The results of this study showed that the English teacher always (100%) used divergent questions in class in the middle and at the end of learning process. The goals were to know students’ opinion, develop their critical and creative thinking skills and improve their knowledge. Further, the teacher usually (80%) used procedural questions in the beginning of the lesson to maintain time management, check students’ conditions and class routine. Finally, the teacher sometimes (60%) used convergent questions to get short answers from the students and help them recalled the material.